IDENTIFIKASI Candida spp. DARI SAMPEL CAIRAN BRONCHOALVEOLAR LAVAGE (BAL) PASIEN INFEKSI SALURAN PERNAPASAN BAWAH: Indonesia - Ririn Feriana Basri; Sitti Rahbiah Akram; Harisa Rama Yanti; Riyan Sukma (Jurnal Biogenerasi, 2023)
Candida spp. it has been possessed of different virulence and resistance patterns in each species, C. albicans remains the main pathogen in infected hosts, but non-albicans Candida also tries with infection. This study aimed to identify Candida species in the bronchoalveolar lavage fluid (BAL) sample of patients with lower respiratory infections with the method of multiplex PCR (Polymerase Chain Reaction). This study was a descriptive and analytical study with a cross-sectional approach, with BAL samples taken from Wahidin Sudirohusodo Hospital. Identification method using multiplex PCR, beginning with screening through culture as the gold standard. Culture on SDA (Sabouraud Dextrose Agar) media from 103 samples of bronchoalveolar lavage fluid (BAL), including 23 samples (22.3%) positive for Candida spp., and positive results related to genotype with multiplex PCR, including 10/23 (43, 5%) C. albicans, and 5/23 (21.7%) C. albicans + C. glabrata. As much as 65.2 % Candida spp. found in males.